The endogenous ecotropic murine retroviruses Emv-16 and Emv-17 are both capable of producing new proviral insertions in the mouse genome. - Szabo, C (1993)
New germ line proviral insertions are acquired at a high frequency by the progeny of SWR/J-RF/J hybrid female mice that carry the endogenous ecotropic murine leukemia proviruses Emv-16 and Emv-17. The tight linkage of these RF/J strain proviral loci has prevented genetic segregation of the retroviral genomes. Hence, it is not known whether both of these proviruses are capable of giving rise to new proviral insertions. We have molecularly cloned Emv-16 and Emv-17 and have characterized them in vitro and in vivo. Restriction enzyme analysis of the recombinant clones revealed that the proviral genomes are very similar to each other and closely resemble the wild-type AKR virus. A comparison of the flanking cellular DNA suggests that the Emv-16 and Emv-17 loci did not arise by simple duplication of a viral insertion site within the RF/J genome but most likely are independent integration events. Both proviruses produce infectious virus when transfected into NIH 3T3 cells, indicating that they are nondefective retroviruses. Exogenous infection of SWR/J mice with either Emv-16 or Emv-17 leads to viremia in the host animals, and in both cases, progeny of viremic females acquire new proviral insertions. The ability of these retroviruses to generate novel retroviral integration sites in the mouse genome provides a simple method for inducing insertional mutations in mice.